Verbrechen gegen die Menschlichkeit durch Migrationskontrolle? Eine völkerstrafrechtliche Untersuchung zur Situation an den südlichen EU-Außengrenzen - Förster, Stine von (Hamburg University Press, 2019)
In her work, Stine von Förster examines the actions of state forces in migration control in Spain, Italy, Greece and Bulgaria. The focus is on the relevance under international criminal law of the handling of migrants in direct connection with irregular entry into the European Union. When examining the events at the borders of the southern EU member states, incidents on the Mediterranean Sea - i.e. before the actual border crossing - as well as the handling of irregular migrants directly following the border crossing are also taken into account. The main subject of the study is the question of whether the handling of irregular migrants at the southern external borders of the EU results in crimes against humanity as defined in Article 7 of the Rome Statute of the International Criminal Court by state forces.